Reduced Frequency of Cases with Seclusion Is Associated with “Opening the Doors” of a Psychiatric Intensive Care Unit - Hochstrasser, Lisa; Voulgaris, Alexander; Möller, Julian; Zimmermann, Tatjana; Steinauer, Regine; Borgwardt, Stefan; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2018)
Background: Implementing an open door policy is a complex intervention comprising changes in therapeutic stance, team processes, and a change from locked to open doors. Recent studies show that it can lead to a reduction of seclusion and forced medication, but the role of the physical change of door status is still unclear. Aims: To examine the transition from closed to predominantly open doors on a psychiatric intensive care unit (PICU) and its associations with the frequency of seclusion and forced medication. Method: A PICU at the Department of Adult Psychiatry, University of Basel, Switzerland, implemented evidence-based strategies for operating an open door policy within the context of acute psychiatry and participated in a hospital-wide implementation of an open door policy before changing door status. 131 inpatient cases hospitalized on this PICU were examined regarding the frequency of seclusion and forced medication using explorative analyses over a time span of 32 weeks (16 weeks after implementation of the new treatment concept but before door opening, 16 weeks after door opening). Results: Following door status change, the PICU was completely open on 51% of the days, and partly open on 23% of the days. The mean number of open hours per day was 12.8 ± 3.9 hours. The frequency of forced medication did not change, the frequency of seclusion decreased significantly (χ2 (1, N = 131) = 4.73, p = .036). Conclusion: This pilot study underlines the potential of a change of door status to attain a reduction in safety measures in the first four months. Declaration of interest: The authors declare no conflict of interest.